Mitochondrial genes associated with cytoplasmic male sterility in Lolium perenne - McDermott, Paul (Trinity College (Dublin, Ireland). Department of Genetics, 2008)
This study involved molecular investigations of cytoplasmic male sterility (CMS) in perennial ryegrass (Lolium perenne L). The CMS line originated as an interspecific hybrid between L. perenne (male parent) and Festuca pratensis (female parent) that was subsequently backcrossed to L. perenne over 9 generations. CMS is a maternally inherited trait in which plants fail to produce functional pollen, often because of rearrangements of the mitochondrial genome that give rise to chimeric genes coding for mitotoxic polypeptides. Chimeric genes have been causally implicated in male sterility in several CMS systems including those of maize, sunflower, radish and petunia. In the case of L. perenne, previous work identified a unique 9.6 kb element called CMSi that was present only in the mitochondrial genome of CMS lines. Nucleotide sequence analysis revealed a chimeric gene, orfC9, near the leftmost junction between CMSi and mtDNA that was shown to be co-transcribed with the normal upstream atp9 gene. Thus, in L. perenne, orfC9 represents a potential CMS-determining gene. This hypothesis was investigated by comparing atp9/orfC9 expression and transcript editing in male-sterile plants and in plants that contained a CMS cytoplasm and a nuclear restorer-of-fertility (Rf) gene. However, no differences between CMS and fertility-restored lines were observed. Nevertheless, attempts to transgenically induce a male-sterile phenotype by targeting the ORFC 9 protein to mitochondria of Nicotiana tahacum resulted in some transgenic lines that exhibited male sterility.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin